Developing insights into the mechanisms of evolution of bacterial pathogens from whole-genome sequences. (November 2012) - Bryant, Josephine; Chewapreecha, Claire; Bentley, Stephen D
Evolution of bacterial pathogen populations has been detected in a variety of ways including phenotypic tests, such as metabolic activity, reaction to antisera and drug resistance and genotypic tests that measure variation in chromosome structure, repetitive loci and individual gene sequences. While informative, these methods only capture a small subset of the total variation and, therefore, have limited resolution. Advances in sequencing technologies have made it feasible to capture whole-genome sequence variation for each sample under study, providing the potential to detect all changes at all positions in the genome from single nucleotide changes to large-scale insertions and deletions. In this review, we focus on recent work that has applied this powerful new approach and summarize some of the advances that this has brought in our understanding of the details of how bacterial pathogens evolve.